2017
DOI: 10.1590/1518-8345.2258.2958
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and anxiety in women with breast cancer before and after treatment

Abstract: Objectives:to determine the quality of life and anxiety in patients with breast cancer and the changes they experience after treatments. Method:prospective study. Breast cancer statistics (n=339, confidence=95%, accuracy= ± 5.32%). The quality of life questionnaires (QLQ) used were QLQ C-30 and QLQ Br23, and the State-Trait Anxiety Inventory (STAI) was used for anxiety. A multivariate analysis was performed to identify variables associated with baseline quality of life and anxiety as well as pre- and post-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
27

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 44 publications
3
51
0
27
Order By: Relevance
“…The extent of the surgical intervention, whether complete mastectomy or breast-conserving therapy, has a negative effect on body image, sexual relations, and social activities, and it can be said that a breast cancer diagnosis represents one predictor of depression 21 . As society favors physical appearance and attractiveness, it is generally accepted that surgical intervention leads to an impaired QoL, including social interactions [22][23][24] . Psychological effects can have an influence on breast cancer patients' day-to-day lives and can affect their social and vocational interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of the surgical intervention, whether complete mastectomy or breast-conserving therapy, has a negative effect on body image, sexual relations, and social activities, and it can be said that a breast cancer diagnosis represents one predictor of depression 21 . As society favors physical appearance and attractiveness, it is generally accepted that surgical intervention leads to an impaired QoL, including social interactions [22][23][24] . Psychological effects can have an influence on breast cancer patients' day-to-day lives and can affect their social and vocational interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This result is inconsistent with previous studies according to which the higher the educational level of women with breast cancer, the better the level of QoL they experience. Timperi et al (2013) found that women with breast cancer had better QoL than patients who had a low educational level while others highlight that the high educational level helps them to have better access to information, a better set of tools and disease management strategies (Villar et al, 2017). Regarding the role of educational level in the perceived social support of women patients regardless of the group they belong to, we found no statistically significant differences between the two groups.…”
Section: Discussionmentioning
confidence: 56%
“…Revista Brasileira de Cancerologia 2019; 65(3): e-12713 e vascular. Resultados similares foram obtidos em outras populações 12,14 . Em um estudo de coorte com 542 mulheres dinamarquesas ao diagnóstico de câncer de mama, em sua maioria com estádio clínico I (31%) ou II (41%), 10% apresentavam uma comorbidade e 10% apresentavam ≥2 comorbidades (aferidas pelo Índice de Comorbidade de Charlson [ICC]).…”
Section: -7unclassified
“…Em estudo realizado com 339 mulheres espanholas diagnosticadas com câncer de mama, sendo a maioria com estádios I (44,3%) e II (38,1%), a média do escore de saúde global foi de 69,2 (± 21,1) e melhores escores foram obtidos nas escalas de função física (92,3±12,4) e função geral (93,3±14,3), e piores escores nos sintomas de insônia (31,7±29,8) e fadiga (15,8±17,5). As mulheres com pior escore de saúde global apresentaram risco 2,07 vezes maior de apresentar comorbidades aferidas pelo ICC (OR=2,07 IC 95% 1,29-3,30) 14 .…”
Section: -7unclassified
See 1 more Smart Citation